Radical innovation in Marshallian industrial districts. Issue 10 (3rd October 2018) - Hervás-Oliver, Jose-Luis; Albors-Garrigos, Jose; Estelles-Miguel, Sofia; Boronat-Moll, Carles
ABSTRACT: Radical innovation is under-researched in the geography of innovation. In this paper, the focus is on understanding how radical innovations occur in Marshallian industrial districts (MIDs), a phenomenon mostly overlooked. Using an exploratory and in-depth longitudinal case study methodology in two European MIDs, this paper analyzes radical innovation in MIDs and finds that the introduction of technology-distant knowledge and new firms from different (to the focal) industries are both necessary mechanisms, but not sufficient. Access to leading incumbents' networks, based on social norms, becomes a crucial social factor necessary for radical innovation to occur in MIDs.